Investigating Opportunities and Challenges of Self-Directed Learning Through TikTok: EFL Students' Perception - Rowiyah , Siti; Cahyono , Bambang Yudi; Laksmi, Ekaning Dewanti (UNIB Press, 2025)
TikTok has become a prominent social media platform, which is notable for its engaging features that display short and fascinating videos. This study aims to investigate the opportunities and challenges confronted by students using TikTok for self-directed language learning. This research employed an interpretative phenomenological analysis design to systematically explain and directly answer the research questions through in-depth group interviews with eight participants who were EFL students with experiences in self-directed language learning using TikTok. The findings of this study revealed that there are many opportunities presented by TikTok for self-directed language learning, including time efficiency, practical and creative application, and its capability to improve students’ English skills through authentic, credible, and memorable lessons. Despite these opportunities, students face several main challenges when using TikTok for language learning, including difficulty in controlling discipline, distraction from irrelevant content, confusion of English accents across videos, and device constraints. This research has significant implications for educators in using TikTok for students’ self-directed language learning. By understanding the opportunities and challenges associated with using TikTok, educators can provide effective guidance and support to their learners. Further research should explore strategies to maximize the opportunities in the students’ use of TikTok for self-directed English learning and in their selection of language learning content on TikTok.